Expressão de genes relacionados às vias de reparo de danos em fita dupla no DNA em pacientes com síndrome mielodisplásica - Ribeiro Júnior, Howard Lopes (2016)
The myelodysplastic syndrome (MDS) is a group of clonal hematopoietic stem cell disorders characterized by cytopenia (s) peripheral (s), dysplasia of one or more myeloid cell lineages and increased risk of acute myeloid leukemia development. MDS is considered a disease of elderly people, since approximately 80% of patients are over 60 years of diagnosis. The causes of MDS are known only in 15% of cases. With respect to environmental factors such as MDS triggers may be included the use of prior chemotherapy, especially alkylating agents and purine analogs, radiation therapy and smoking. The pathogenesis of MDS involves DNA damage in hematopoietic stem cells affected probably by double-stranded damage (DSB) in the DNA and the case of joints by non-homologous ends (NHEJ) and homologous recombination main repair mechanisms necessary to ensure stability genomics of stem cells. This cohort study aimed to assess the level of expression of mRNA of the genes active in the repair mechanism of double-stranded DNA damage (BRCA1, BRCA2 and RAD51, operating in HR mechanism, the XRCC5, XRCC6 and LIG4 related mechanism for NHEJ and, finally, the ATM) linking the molecular findings with their polymorphic variants (rs4793191, rs9567623, rs1801320, rs3835, rs2267437, rs1805388 and rs228593, respectively) and with clinical and socio-demographic of patients of Myelodysplastic Syndromes. This genotyping analysis was based on qPCR methodology, including bone marrow samples from 83 patients with MDS and 10 bone marrow samples from healthy elderly volunteers. The MDS patients were diagnosed according to the criteria proposed by the World Health Organization and stratified according to the criteria established by prognósitoc Score Index International Prognostic revised. In this study we observed that: 1. the ATM, BRCA1, BRCA2 and RAD51 genes were significantly associated with cellularity variable bone marrow of patients with MDS; 2. the XRCC5 gene introduced is associated with the presence of ringed sideroblasts on the analysis of the bone marrow of patients with MDS; 3. The BRCA2, RAD51 and LIG4 genes correspond to potential markers of poor prognosis and progression in clonal cases of MDS de novo of high level, being associated with decreased survival and a high chance of progression to AML; 4. the XRCC6 gene is a negative prognostic factor for patients at low risk, it is evident that the decrease in expression of this gene is able to identify an unfavorable subgroup within the low-risk patients who have higher dependence transfusion and increased genomic instability and finally, 5 the results of analysis of influence of functional polymorphisms in MDS emphasize the importance of polymorphism rs228593, rs2267437 and rs1805388 in differentiating the expression levels of ATM, XRCC6 and LIG4 genes, respectively, compared to patients with clinical variables MDS representing novel targets for the study of the pathogenesis of this disease. We demonstrate that the DSBs repair related genes are also related to the pathogenesis of MDS. These results support the importance of the expression levels of ATM, BRCA1, BRCA2, RAD51, XRCC5, XRCC6 and LIG4 genes, as well as the frequency of the respective polymorphisms (rs228593, rs4793191, rs9567623, rs1801320, rs3835, rs2267437 and rs1805388) in the maintenance genomic stability of hematopoietic stem cells promoting a better understanding of the etiology, diagnosis and prognostic stratification and the process of clinical development of Myelodysplastic Syndromes.